An isolated Xp deletion is linked to autoimmune diseases in Turner syndrome - Stoklasova, Judith; Zapletalova, Jirina; Frysak, Zdenek; Hana, Vaclav; Cap, Jan; Pavlikova, Marketa; Soucek, Ondrej; Lebl, Jan (Journal of pediatric endocrinology & metabolism, 2019)
Background Females with Turner syndrome (TS) are prone to develop autoimmune diseases (AIDs). The X chromosome contains several immune-related genes. Growth hormone (GH) and estrogens modulate the immune system. We aimed to clarify whether the loss of a specific X chromosome gene locus and the administration of GH and estradiol facilitate the development of AIDs in TS females. Methods Retrospective data on clinical course, AIDs, karyotype and treatment were analyzed from a cohort of 286 Czech females with TS (current age 2.8-43.3 years; median age 18.7 years). The karyotypes were sorted using two different classification systems: a mosaicism-focused and an isochromosome (isoXq)-focused approach. Karyotype subgroups with a significantly higher prevalence of AIDs were further evaluated. Data of common therapies were correlated with the prevalence of AIDs. Results The most frequent AIDs were autoimmune thyroid disease (AITD; 37.4%; n = 107) and celiac disease (CD; 8.7%; n = 25). All karyotype subgroups were prone to develop AIDs. Females with an isolated Xp deletion had a significantly higher prevalence of AITD and CD compared to all other individuals with TS (AITD: 66.0% vs. 31.5%, p < 0.0001; CD: 17.4% vs. 7.2%; p = 0.04, respectively). We observed no link between the mean age at initiation as well as the duration of GH and/or estrogen administration and the occurrence of AIDs. Conclusions Isolated Xp deletion contributes to the development of AIDs in TS patients. The haploinsufficiency of genes located in Xpter-p11.2 may explain this observation. Common therapies used in TS do not modify the risk of AIDs.
Keywords: autoimunitní nemoci; Humans; dítě; Turner syndrome; isolated Xp deletion; prevalence; Child; Female; mladý dospělý; dospělí; genetics; lidé; lidské chromozomy X; Autoimmune Diseases; předškolní dítě; Adult; karyotype; Follow-Up Studies; ženské pohlaví; chromozomální delece; Turnerův syndrom; Chromosome Deletion; Retrospective Studies; Adolescent; prognóza; celiac disease; Chromosomes, Human, X; Czech Republic; Turner Syndrome; Young Adult; karyotypizace; Prevalence; retrospektivní studie; Česká republika; autoimmune thyroid disease; Child, Preschool; Karyotyping; Prognosis; následné studie; mladiství